PENGARUH ETIKA DAN MORAL DALAM PROSES HUKUM :KASUS KOLABORASI RICHARD ELIEZER DALAM KASUS PEMBUNUHAN NOFRIANSYAH YOSWA - Nur Kholis; Askana Fikriana (PROGRAM STUDI ILMU KOMUNIKASI, 2023)
This research focuses on the significant role played by a Justice Collaborator in a controversial murder case involving Bharada Richard Eliezer in Indonesia. The author discusses the importance of the Justice Collaborator's contribution in unraveling complex criminal cases while exploring various ethical and moral questions that arise in the context of the judiciary. This case underscores the need to maintain a balance between formal law, ethics, and morality within the judicial system, which, in turn, influences the creation of legislation, legal decision-making, and public perception. Consequently, it can be concluded that it is essential to emphasize the consideration of ethics and morals as key factors within the legal system to uphold integrity and meet societal expectations. This conclusion reflects the intricacies of the Justice Collaborator's role and the impact of ethics and morality within the realm of the judiciary. In a broader context, this research serves as a reminder of the integral role that a Justice Collaborator plays in ensuring justice and integrity within the modern judicial system.